2021
DOI: 10.3897/zookeys.1024.60473
|View full text |Cite
|
Sign up to set email alerts
|

A new species of leaf-toed gecko (Phyllodactylidae, Phyllodactylus) from María Cleofas Island, Nayarit, Mexico

Abstract: We describe a new species of leaf-toed gecko of the genus Phyllodactylus from María Cleofas Island, the smallest island of Tres Marías Archipelago, Nayarit, México. Genomic, phylogenomic, and morphological evidence support that the new species presents a unique combination of diagnostic characters. Morphologically, the new species has a high number of tubercles, head to tail (mean 47), longitudinal ventral scales (mean 61), and third labial–snout scales (mean 26). Gene flow tests revealed the genetic isolation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 1,088 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…Zweifel (1960) proposed that Urosaurus ornatus reached most of the Islas Marías archipelago by dispersal over water from mainland populations in Sinaloa. Recent studies of the genomics and phylogenomics of leaf-toed geckos (genus Phyllodactylus Gray, 1828), showed that P. cleofasensis diverged from mainland populations about 7 Ma ago (Ramírez-Reyes et al 2020, 2021a, but, most surprisingly, its sister species is P. saxatilis (Dixon, 1964) from Villa Unión, Sinaloa. All of this suggests that the reptile diversity in the archipelago is more complex than has been previously envisioned.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zweifel (1960) proposed that Urosaurus ornatus reached most of the Islas Marías archipelago by dispersal over water from mainland populations in Sinaloa. Recent studies of the genomics and phylogenomics of leaf-toed geckos (genus Phyllodactylus Gray, 1828), showed that P. cleofasensis diverged from mainland populations about 7 Ma ago (Ramírez-Reyes et al 2020, 2021a, but, most surprisingly, its sister species is P. saxatilis (Dixon, 1964) from Villa Unión, Sinaloa. All of this suggests that the reptile diversity in the archipelago is more complex than has been previously envisioned.…”
Section: Discussionmentioning
confidence: 99%
“…The above-referenced studies exclude the Islas Marias Archipelago Biosphere Reserve, which is one of the most herpetological diverse land-bridge islands in the Mexican Pacific (Pliego-Sánchez et al 2021). To our knowledge, there seems to be a consensus among herpetologists that amphibians and reptiles from the Mexican Central Pacific islands are representatives of taxa found on the adjacent mainland (Zweifel 1960;Casas-Andreu 1992;Woolrich-Piña et al 2016;Pliego-Sánchez et al 2021), but they also recognize that different ecological and evolutionary pressures could have influenced morphological and behavioral traits of these insular populations (Rodríguez and Drummond 2000;Senczuk et al 2014;Siliceo-Cantero et al 2016;Ramírez-Reyes et al 2021a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…nov. for populations from the type locality (Villa Union, Sinaloa sensu Dixon, 1964) and the nearest population from Cosala, Sinaloa (Figure 4), differentiated from a possible new species inhabiting lowlands of Sonora. The formal description of the lineage that inhabits the island of Maria Cleofas was elaborated, mainly due to the evidence of remarkable genetic isolation (Ramírez‐Reyes et al., 2021). Finally, greater population and genomic sampling is required to identify the evolutionary processes that best explain the close relationship that exists in insular and continental taxa Phyllodactylus in Northwest Mexico, and in particular the close relationship among P. partidus , P. homolepidurus, P. nolascoensis and some lineages of Phyllodactylus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Recent phylogenetic studies on Mexican islands led to the description of two insular endemic rattlesnakes (Meik et al, 2018), the elevation to species of synonymous insular snake populations (Cox et al, 2018), and the proposal to elevate three subspecies of island geckos (recognized as subspecies by Ramírez- Reyes et al, 2021;Ramírez-Reyes & Flores-Villela, 2018;Uetz & Hošek, 2020).…”
Section: Biogeographic Patternsmentioning
confidence: 99%